Physical oceanographic profiles of 5 CTD casts during RV MARIA S. MERIAN cruise MSM127/1 off Gran Canaria in March 2024 - Tim Freudenthal (PANGAEA, 2025)
During cruise MSM127/1 of the RV MARIA S. MERIAN from 08 to 13 March 2024, the CTD/rosette (type Seabird SBE911plus with SBE-32 rosette) was deployed 5 times in the Canary Islands region for technical tests. The collected CTD data set include water temperature, salinity, oxygen concentration, and fluorescence.